Improving Cognition through Dance in Older Filipinos with Mild Cognitive Impairment - Dominguez, Jacqueline C.; del Moral, Maria Clarissa O.; Chio, Jeshya Obeso A.; de Guzman, Ma. Fe P.; Natividad, Boots P.; Decena, Jay-Pee M.; Montalvo, Maryanne Jenelle Y.; Reandelar, Macario; Phung, Kieu T.T. (Current Alzheimer Research, 2018)
Background: People with mild cognitive impairment (MCI) are considered a high-risk population for developing dementia and therefore potential targets for preventive interventions. So far, no pharmacological interventions have proven to be effective. Latest evidence has laid the groundwork for the hypothesis that dancing can have beneficial effect on cognition by improving neuroplasticity. Objective: This study aimed to examine whether a structured modular ballroom dance intervention (INDAK) could improve cognition among Filipino older persons with MCI. Methods: A two-armed, single-blinded, quasi-experimental study was conducted in a community-based population at Marikina City, Philippines. Two hundred and seven participants older than 60 years old with MCI participated through self-assigned allocation to dance (N=101) and control (N=106) groups. The intervention group received INDAK consisting eight types of ballroom dances with increasing complexity lasting one hour, twice a week for 48 weeks. Neurologists and psychologists blinded to the group allocation administered baseline and post intervention assessments using Alzheimer's Disease Assessment Scale – Cognitive (ADAS-Cog), Filipino version of the Montreal Cognitive Assessment (MoCA-P), Boston Naming Test (BNT), Geriatric Depression Scale (GDS), Instrumental Activities of Daily Living (IADL) and Disability Assessment for Dementia (DAD). Results: Baseline sociodemographic and clinical characteristics did not differ between groups. The mean differences between baseline and 48-week assessments were compared between dancers and controls, showing that the intervention group improved in ADAS-Cog, MoCA-P, BNT and GDS. Conclusion: INDAK is potentially a novel, ecological and inexpensive non-pharmacological intervention that can improve cognition among older Filipinos with MCI.
Keywords: non-pharmacological intervention